التنغيم والسياق و أثرهما في فهم الخطاب الشعري الحديث قصيدة "منشورات فدائية" لنزار قباني أنموذجا (Revue El-Wahat pour les Recherches et les Etudes, 2017)
This paper attempts to study one of most important prosodic elements which is "intonation" .it seeks to reveal how the poetic performance responds to intonation through  some passages of NizarQabbani's poem. This objective can be reached only by investigating some of the concepts that tried to present specific definitions .The study also provides an integrative vision that reveals the coherence between intonation, and the context of the poem. Key Terms - intonation, poetic performance, context, rhetoric.